Renal mitochondrial oxidative stress is enhanced by the reduction of Sirt3 activity, in Zucker diabetic fatty rats. (1st January 2018) - Ogura, Yoshio; Kitada, Munehiro; Monno, Itaru; Kanasaki, Keizo; Watanabe, Ai; Koya, Daisuke
ABSTRACT: Objectives: Mitochondrial oxidative stress is involved in the pathogenesis of diabetic kidney disease. The objective of our study is to identify the mechanisms of renal mitochondrial oxidative stress, focusing on Sirt3, which is nicotinamide adenine dinucleotide (NAD + ; oxidized NAD)-dependent deacetylase in mitochondria. Methods: Renal mitochondrial oxidative stress and Sirt3 activity, using Zucker diabetic fatty rats (ZDFRs) and cultured proximal tubular cells under high-glucose condition were evaluated. Results: At 28 weeks of age, ZDFRs exhibited the increased urinary albumin/liver-type fatty acid-binding protein (L-FABP)/8-hydroxy-2'-deoxyguanosine (8-OHdG) excretion, histological tubular cell damage, compared to non-diabetic Zucker Lean rats. In renal mitochondria, acetylated isocitrate dehydrogenase2 (IDH2) and superoxide dismutase2 (SOD2), accompanied with mitochondrial oxidative stress and mitochondrial morphologic alterations, were increased in ZDFRs, indicating inactivation of Sirt3. Additionally, expression of the NAD-degrading enzyme, CD38, was increased, and the NAD + /NADH (reduced NAD) ratio was reduced in the renal cortex of ZDFRs. High-glucose stimulation in cultured proximal tubular cells also resulted in an increase in acetylated IDH2/SOD2, CD38 overexpression and a reduction in the NAD + /NADH ratio. Conclusions: Enhancement of mitochondrial oxidative stress in the diabetic kidney was mediated by the reduction of Sirt3 activity. CD38 overexpression may be related to a reduction in the NAD + /NADH ratio in the diabetic kidney.